2001
DOI: 10.1080/02626660109492833
|View full text |Cite
|
Sign up to set email alerts
|

Monthly runoff prediction using phase space reconstruction

Abstract: A nonlinear prediction method, developed based on the ideas gained from deterministic chaos theory, is employed: (a) to predict monthly runoff; and (b) to detect the possible presence of chaos in runoff dynamics. The method first reconstructs the single-dimensional (or variable) runoff series in a multi-dimensional phase space to represent its dynamics, and then uses a local polynomial approach to make predictions. Monthly runoff series observed at the Coaracy Nunes/Araguari River basin in northern Brazil is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 18 publications
1
34
1
Order By: Relevance
“…This has further been verified and supported by the near-accurate predictions achieved for streamflow data observed at different river systems (e.g. Porporato and Ridolfi, 1997;Jayawardena and Gurung, 2000;Sivakumar et al, 2001aSivakumar et al, , 2002aLisi and Villi, 2001;Islam and Sivakumar, 2002) and also for other hydrologic and geomorphic data, such as lake volume (e.g. Abarbanel and Lall, 1996) and suspended sediment concentration (e.g.…”
Section: Introductionmentioning
confidence: 49%
See 2 more Smart Citations
“…This has further been verified and supported by the near-accurate predictions achieved for streamflow data observed at different river systems (e.g. Porporato and Ridolfi, 1997;Jayawardena and Gurung, 2000;Sivakumar et al, 2001aSivakumar et al, , 2002aLisi and Villi, 2001;Islam and Sivakumar, 2002) and also for other hydrologic and geomorphic data, such as lake volume (e.g. Abarbanel and Lall, 1996) and suspended sediment concentration (e.g.…”
Section: Introductionmentioning
confidence: 49%
“…Schreiber and Kantz, 1996), such a theoretical expectation is difficult to meet with when one deals with real data, which are always contaminated with noise. The effect of noise (on prediction/disaggregation) with respect to embedding dimension and number of neighbors are discussed in detail in Sivakumar et al (1999Sivakumar et al ( , 2001aSivakumar et al ( , b, 2002a and, therefore, are not reported herein.…”
Section: Disaggregation Of Flow From 2-day To Dailymentioning
confidence: 99%
See 1 more Smart Citation
“…Jayawardena and Lai, 1994), flood (Laio et al, 2003), and streamflow on daily and monthly scales (e.g. Jayawardena and Lai, 1994;Porporato and Ridolfi, 1996, 2001Liu et al, 1998;Sivakumar et al, 2001Sivakumar et al, , 2002. However, in other fields, especially, medical, there are widespread forecast applications (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Jayawardena & Lai, 1994;Porporato & Ridolfi, 1997;Krasovskaia et al, 1999;Stehlik, 1999;Sivakumar et al, 2002); the possibility of accurate river flow predictions using nonlinear deterministic approaches (e.g. Porporato & Ridolfi, 1997;Sivakumar et al, 2001Sivakumar et al, , 2002; and the superiority of these approaches over stochastic ones (e.g. Jayawardena & Gurung, 2000;Lisi & Villi, 2001).…”
Section: Introductionmentioning
confidence: 99%